Baseline SUVmax of 18F-FDG PET-CT indicates prognosis of extranodal natural killer/T-cell lymphoma. Issue 37 (11th September 2020) - Xia, Xianwu; Wang, Yaqi; Yuan, Jianjun; Sun, Wenjie; Jiang, Jinjin; Liu, Chang; Zhang, Qunling; Ma, Xuejun
Abstract : Abstract: To evaluate the prognostic value of the baseline SUVmax of 18 F-FDG PET-CT in extranodal natural killer/T-cell lymphoma (NKTCL) patients. From January 2010 to December 2015, 141 extranodal NKTCL patients with staging 18 F-FDG PET-CT scan were divided into two group based on SUVmax cutoff value obtained from operating characteristic (ROC) curves. All the patients received radiotherapy, chemotherapy or chemoradiation. Survival analysis was performed on the basis of SUVmax. The median baseline SUVmax of the tumors was 11.67 (range 2.6–34.6). The ROC curves showed that the optimal cutoff of the baseline SUVmax was 9.65. The patients were divided into two groups: low SUV group (SUVmax < 9.65) and high SUV group (SUVmax ≥ 9.65). Patients in high SUV group were more likely to have invasive disease outside the nasal cavity ( P < .001), poorer ECOG scores ( P = .012) and higher LDH levels ( P = .034). The univariate survival analyses indicated that high SUVmax was a poor prognostic factor for overall survival (OS, P = .038), progression free survival (PFS, P = .006) and distant relapse free survival (DRFS, P = .001), but not for local recurrence free survival (LRFS, P > .05). These results were consistent with that of the survival analyses using the Kaplan–Meier method. The multivariate survival analyses showed that the baseline SUVmax was no longer a prognostic factor for OS (HR 1.99, 95% CI 0.81–4.88, P = .135), but it still indicated worse PFS (HR 2.6, 95% CI 1.24–5.46, P = .012) and DRFS (HR 4.58, 95% CI 1.83–11.46, P = .001) independent of other variables. For extranodal NKTCL patients, a higher baseline SUVmax of 18 F-FDG PET-CT was associated with more aggressive clinical features. An SUVmax ≥ 9.65 was an independent poor prognostic factor for DRFS and PFS. Thus, the baseline SUVmax may be a valuable tool to help identify patients with a high risk of disease progression. Abstract : Supplemental Digital Content is available in the text